2018
DOI: 10.1155/2018/1424275
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Thoracoscopic Resection of a Posterior Mediastinal Mullerian Cyst

Abstract: First described in 2005, the Mullerian derived cyst in the mediastinum is a rare finding with few subsequent reports. We report a case of Mullerian cyst occurring in the mediastinum of a 49-year-old female that was resected by robot-assisted thoracoscopic surgery. To our knowledge, this is the first report of robot-assisted resection of Hattori's cyst. Histopathologic analysis revealed ciliated Mullerian-type tubal epithelium positive for paired box gene 8 (PAX8), estrogen receptor (ER), and progesterone recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…The immunohistochemical profile demonstrated positivity to oestrogen as well as progesterone receptors. Such cysts, in relation to this condition, were first described by Hattori in 2005 as being female sex hormone receptor sensitive and situated in the posterior mediastinum [4].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The immunohistochemical profile demonstrated positivity to oestrogen as well as progesterone receptors. Such cysts, in relation to this condition, were first described by Hattori in 2005 as being female sex hormone receptor sensitive and situated in the posterior mediastinum [4].…”
Section: Introductionmentioning
confidence: 95%
“…The pathogenesis of Müllerian cysts, which are located in the posterior mediastinum, is not yet fully understood. It was suggested by Ludwig et al in his study of Mayer-Rokitansky-Kuster-Hauser syndrome [1][2][3], that such cysts are possibly remnants of embryonic Müllerian tissue. The pathomorphology showed that the cysts were lined with ciliated columnar/tubal epithelium surrounded by a thin smooth muscular layer (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the patient of the present study, barium in the upper gastrointestinal tract indicated that the esophagus was compressed by the mass, which was further identified by EUS as a cyst outside the esophageal wall. Furthermore, all examination results inferred that the cyst may be benign and located in the posterior mediastinum, which is least likely to contain a malignant mass in the three mediastinal cavities (11). All of these observations indicated that EUS-FNA could be performed.…”
Section: Discussionmentioning
confidence: 78%
“…Since its approval for cardiac surgery in 2002, RATS has gained traction ( 24 ). There are a number of successful case series of mediastinal cyst and mass excisions using this technique and authors frequently cite the degrees of freedom with the robot arms, removal of the “surgeon’s tremor”, and improved visibility as benefits of this approach ( 25 - 29 ). The described reports below used a 4-port approach unless otherwise specified.…”
Section: Robot-assisted Thoracoscopic Surgery (Rats)mentioning
confidence: 99%
“…A 2-cm posterior Mullerian cyst along the right anterolateral aspect of T5 vertebral body was able to be successfully excised in the left lateral decubitus position via the RATS approach and was able to be discharged on POD2. The surgeons chose the robot-assisted approach because of the “precise manipulation of the machine arms” and magnification that allowed them to separate the cyst from the spine without damage to neighboring veins ( 25 ).…”
Section: Robot-assisted Thoracoscopic Surgery (Rats)mentioning
confidence: 99%